Analysis of Life Insurance Company Financial Performance: Early Warning System Ratios and Risk-Based Capital Before and After the Covid-19 Pandemic in Indonesia - Ayunda Annisa Soleha; Made Irma Lestari (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2025)
This study aims to analyze the financial performance of life insurance companies through the early warning system ratios and risk-based capital before (2019) and after the pandemic (2023). Utilizing a quantitative research approach with purposive sampling, a total of 44 samples were tested in this study as non parametric data. The data analysis method employed is descriptive analysis using the non-parametric wilcoxon signed rank test, conducted with IBM SPSS Statistics software. The results indicate that there were no significant changes in the combined ratio, retention ratio, liquidity ratio, technical reserve ratio, and risk-based capital ratio, although some positive trends were observed. Meanwhile, the investment adequacy ratio experienced a significant decline but remained within a healthy category. Overall, these findings reflect the life insurance industry's ability to stabilize its financial performance through strategic adaptation following the Covid-19 pandemic.